2018
DOI: 10.1186/s41610-018-0098-8
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and habitat use of gelada baboon (Theropithecus gelada) in Wof-Washa Forest (Gosh-Meda Area), Central Ethiopia

Abstract: Background: Gelada baboon is one of the endemic mammals of Ethiopia residing in different highlands. The population structure and habitat use of gelada baboon in Wof-Washa particularly Gosh Meda area was investigated from September 2016 to August 2017. Total counting method was used to collect data on the population status by dividing the study area in to four blocks, namely, Kundi, Arbgebeya, Goshber, and Goshmeda. Data were analyzed using SPSS software. The age-sex category and the numbers of geladas found w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
(11 reference statements)
2
10
0
Order By: Relevance
“…Geladas differ from baboons by the bright patch of skin on their chest [ 24 , 25 ]. The habitat is characterized by its vicinity to cliffs for sleeping and the use of several different types of relatively treeless and montane grasslands for foraging; habitats that are usually intermixed with bushes, trees, and dens thickets [ 26 29 ]. Among primates, geladas are excellent diggers and the only primate which has a specialized graminivorous diet [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Geladas differ from baboons by the bright patch of skin on their chest [ 24 , 25 ]. The habitat is characterized by its vicinity to cliffs for sleeping and the use of several different types of relatively treeless and montane grasslands for foraging; habitats that are usually intermixed with bushes, trees, and dens thickets [ 26 29 ]. Among primates, geladas are excellent diggers and the only primate which has a specialized graminivorous diet [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we reported the highest relative abundance of juvenile population size compared to a study in Gosh-Meda area, central Ethiopia [ 17 ] and Debre-Libanos [ 28 ] . This implies that there is a promising population structure despite the underlying anthropogenic threats in these mountain clusters.…”
Section: Discussionmentioning
confidence: 58%
“…Previously, geladas were believed to be range limited to the well-known and relatively accessible regions of Bale and the Simien Mountain national park. There have been several empirical studies on the gelada population structure [ 13 , [16] , [17] , [18] ], ecology [ [19] , [20] , [21] ], phylogeography [ 22 ] and distribution [ 2 , 23 ] from different localities in Ethiopia. Nevertheless, despite the historical records and museum collections indicating the historical presence of the gelada in Tigray [ 2 , 23 ], Tigray has been removed from the list of gelada home ranges [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The total count method of population census was used to determine the population size and structure of gelada in the study area. Total population census/count has been reported to be effective to determine the population size of gelada in open habitat type, where there is good visibility of individuals of gelada in various localities (Abu, 2011; Adem, 2009; Ayalew, 2009; Beehner et al, 2008; Girmay & Dati, 2020; Goshme & Yihune, 2018; Kifle et al, 2013; Moges, 2015). Likewise, the present study area is a predominately open habitat that allows reasonable visibility of individuals of gelada.…”
Section: Methodsmentioning
confidence: 99%
“…The second largest population of gelada is found in Menz Guassa Community Conservation Area (MGCCA; Moges, 2015). More recently, populations of gelada are reported from Wof‐Washa Forest (Gosh‐Meda Area), central Ethiopia (Goshme & Yihune, 2018), from eastern escarpments of Tigray (Girmay & Dati, 2020), and Yegof Forest, South Wollo (Ahmed et al, 2022). Gelada population is limited to the high grassland cliff in the deep gorges in the central plateau, of the Wollo Province such as in Azwa and Arego valleys, Borena Sayint National Park (BSNP) and Mount Abune Yosef Community Conservation Area (MAYCSA; Adem, 2009; Ayalew, 2009; Eshete et al, 2015; Kifle, 2018).…”
Section: Introductionmentioning
confidence: 99%